Hyperuricemic syndromes pathophysiology and therapy - Ronco, Claudio 1951-; Rodeghiero, Francesco (Contributions to nephrology, 2005)
Uric acid disorders are involved in both nephrological and hematological diseases. One of these crystal-associated diseases which has been known since antiquity is gout. More recently, tumor Lysis syndromes have been identified which affect patients with cancer, especially in the phase of cellular destruction after chemotherapy. The detection of these hyperuricemic syndromes, together with the improved understanding of urate handling by the kidney, have spurred new interest in the pathophysiology of hyperuricemic states, their clinical consequences and management. Moreover, the recent development of a recombinant form of urate oxidase transforming uric acid into allantoin (Rasburicase) has caused new interest in the pathophysiology of hyperuricemia and the potential applications of this new drug.The multidisciplinary approach of this book offers new insights into the metabolic syndromes in question by uniting authors from the fields of biochemistry, pharmacology, rheumatology, onco-hematology, and nephrology. The result is a compendium of the present knowledge in the field, which will also be very useful as a reference tool for professionals and students who want to expand their knowledge on this topic